ANALISIS FAKTOR–FAKTOR YANG BERPENGARUH TERHADAP HARGA SAHAM (Studi KasusPada Perusahan Manufaktur Yang Terdaftar di BursaEfek Indonesia) Tahun 2009 - 2012 (Students' Journal of Accounting and Banking, 2014)
This research discusses the influence of the relationship of ROA, EPS, PER, and DER on stock prices, using the object manufacturing company. Sample used was recorded at 116 companies, using purposive random sampling technique. The analytical method used is multiple linear regression analysis method. The analytical tool used was SPSS. Results T-test shows that the variables ROA and EPS has a positive and significant effect on stock prices, while the PER and DER variable has a positive effect and no significant effect on stock prices. Keywords: ROA, EPS, PER, DER and Stock Price